FAKTOR-FAKTOR PENYEBAB TIMBULNYA DISPARITAS PEMIDANAAN - SH.,MH, Amrun, (Menara Ilmu, 2018)
The judge's verdict becomes the most decisive part of the criminal procedure series or inthe operation of the criminal justice system. The judge's verdict is very important because ithas enormous consequences for both convicted person and society in general. In that case,growing disparities in law enforcement in Indonesia.Based on the above description, this study is based on the curiosity of researchers withinthe scope of factors causing the disparity of sentencing. Therefore, this study aims todetermine and analyze the factors causing the disparity of sentencing. The type of this researchis normative law research. The nature of this research is descriptiveThere are 3 (three) factors causing criminal disparity based on the source, that iscriminal disparity that comes from the legal system and the philosophy of punishment, thecriminal disparity that comes from the judge, and the criminal disparity sourced from thedefendant. Therefore, the policy makers in the criminal law should make a guideline for thecriminal prosecution of judges in order to make it easier for judges to determine theirpunishment.Keywords: Judge Verdict, Disparity of Sentencing, Criminal Law Policy